Soft magnetic properties of as-sputtered Fe-Al-O films - Kim, SR; Kim, KH; Jang, YI; Kim, J; Han, SH; Kim, HJ (ELSEVIER SCIENCE BV, 2000)
The magnetic and structural properties of as-sputtered nanocrystalline Fe-Al-O films, fabricated by a magnetron sputtering apparatus, are investigated as a function of the sputtering input power. The saturation magnetization of 19.6 kG are obtained in the Fe95.9Al1.5O2.6 film deposited at 4.9 W/cm(2), and an effective permeability larger than 1000 at 10 MHz in the wide range of the input power. (C) 2000 Elsevier Science B.V. All rights reserved.